Effectiveness of physical activity promotion programme on quality of life for old people - Patil, Priyanka; Patil, Prajakta (International Journal of Research in Medical Sciences, 2017)
Background: The purpose is to evaluate the effectiveness of the Physical Activity Promotion Programme (PAPP) on quality of life for old people. Methods: A total of 43 subjects of both genders participated in the experimental study with convenient sampling; all were aged 55-70 years from Dhanori road, Pune. Participants received the PAPP for 50 minutes daily. The effectiveness of PAPP was measured by short-form 36 questionnaire. Results: This experimental study had a significant impact on quality of life (P = 0.001), in both gender, which was increased. The overall changes improved to 82.3% from 47.8% and mainly in physical functioning & general health by 12.5% and 12% respectively after PAPP and pain was reduced to 26%.Thus, quality of life improved significantly for old people who carried out the PAPP. Conclusion: Quality of life measured with SF- 36 in the group of old people were improved after PAPP.